Strategi Penguatan Brand Image untuk Meningkatkan Daya Saing Lembaga Pendidikan Dasar di Era Digital - Mukhamat Saini; Nurani Rahmania (STAI Miftahul Ula Nganjuk, 2025)
This article presents a systematic literature review to analyze strategies for strengthening the brand image of elementary education institutions in the digital era. The research background is rooted in the increasingly intense competition among institutions and the shifting behavior of parents as more critical consumers of education. This study aims to consolidate findings from various empirical studies to formulate a synthesis of effective strategies. The method used is a systematic literature review with the PRISMA protocol, in which ten journal articles indexed in SINTA 3 to 6 are analyzed thematically. The synthesis results reveal four main, interrelated strategic clusters: first, an integrated digital communication strategy through websites and social media as awareness amplifiers; second, a strategy based on direct experience and community, positioning parents and alumni as core brand ambassadors; third, a differentiation strategy through achievements and flagship programs as competitive differentiators; and fourth, a proactive reputation management strategy to maintain trust. The research conclusion affirms that sustainable brand image building requires a hybrid approach that authentically integrates digital narratives with substantive performance in the field, where the school community acts as an active co-creator. In practical terms, school administrators need to design integrated communication plans and institutionalize stakeholder engagement. This study recommends further research in the context of public schools and rural areas, as well as longitudinal studies to measure the impact of branding strategies on educational outcomes